Framing Pemberitaan Dugaan Penistaan Agama Selebgram Oklin Fia - Saputra, Bagas; Sukmawati, Lilis (NOUMENA: Jurnal Sosial Humaniora dan Keagamaan, 2024)
This research aims to find out, observe and analyze how the framing was carried out by the online media detik.com and tribunnews.com in reporting the alleged blasphemy case of Selebgram Oklin Fia and to make a comparison between the two media. There were 4 news samples studied for each online media. . This research method uses a descriptive qualitative approach with a framing model from Zhongdang Pan and Gerald M. Kosicki, while the data analysis technique used in this research is analysis from Milles and Huberman. The results of this research show that the media detik.dom and tribunnews.com have differences in reporting something. Researchers can conclude that detik.com media is more detailed and focused in reporting cases. Meanwhile, researchers at tribunnews.com media concluded that the media did not focus too much on the cases being reported and tended to use sentences and images that could lead to negative opinions among readers.